Penerapan Instrumen Cash Waqf Linked Sukuk (CWLS) Berdasarkan Prinsip Maslahah Pada BSI - Mukhtar Luthfi; Abdul Wahab; Husni Nasir (Al-Azhar Journal of Islamic Economics, 2022)
Cash Waqf Linked Sukuk (CWLS) is a sukuk investment instrument published by the state called retail SBSN. CWLS is published as one of the efforts by the Government to develop a productive waqf in Indonesia. The innovation in this project by BI, Finance Ministry, Ministry of State-Owned Enterprises, and BWI. The objective of the sukuk based waqf development is to increase its oprational value by getting various parties involved. Cash Waqf is a sharia financial sector that needs to developed for social welfare in Indonesia. The method used in this article is a descriptive field research.